Glass and processing technology and application thereof

By distributing irregular pits on the outer surface of the glass and combining sandblasting and chemical-popping treatment, anti-glare glass is formed, which solves the problem that the glass back cover in the prior art cannot meet the consumer's touch and appearance effect needs, and achieves a glass material with comfortable touch feel and excellent anti-fingerprint effect.

CN119898967APending Publication Date: 2025-04-29BEIJING XIAOMI MOBILE SOFTWARE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311403353.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The battery back cover made of high-brightness glass as the main body in the prior art cannot meet consumers' needs for a more comfortable surface touch and a more gorgeous appearance effect.

Method used

By distributing irregular pits on the outer surface of the glass, combining high-speed airflow sandblasting and chemical-popping treatment, an anti-glare glass body can be formed, and a hydrophobic film layer and ink layer can be optionally attached to enhance the decorative effect.

Benefits of technology

It achieves anti-glare glass with comfortable touch and good texture on the surface sand grain, excellent anti-fingerprint effect, and is suitable for electronic equipment shells to enhance the appearance, texture and touch.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898967A_ABST
    Figure CN119898967A_ABST
Patent Text Reader

Abstract

The invention relates to glass as well as a processing technology and application thereof. The glass comprises a glass main body, wherein a plurality of irregular pits are distributed on the outer surface of the glass main body; wherein the roughness of the glass ranges from 0.8 to 1.2, and the haze of the glass ranges from 70 to 85; the processing technology comprises the following steps: carrying out sand blasting treatment on the outer surface of a glass substrate by using high-speed airflow containing carborundum to obtain first glass with pits in the outer surface; carrying out chemical polishing treatment on the outer surface of the first glass to obtain second glass with an anti-glare effect on the outer surface; wherein the chemical polishing treatment comprises the step of carrying out chemical etching on the outer surface of the first glass by using a solution containing H < + > or a solution containing OH <->. The glass provided by the invention is excellent in anti-fingerprint effect, comfortable in touch hand feeling and good in surface sand grain texture, and can be applied to an electronic equipment shell, so that the appearance, texture and touch sense of the electronic equipment shell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of terminal device housings, and in particular to glass and a processing technology and application thereof. Background Art

[0002] At present, the battery cover of electronic devices is mostly made of glass, plate and other materials. Among them, glass is the main material. By making different appearance decoration processes on the outer and inner surfaces of the glass, more decorative elements can be added to the entire battery cover. For battery back covers based on glass as the main material, consumers tend to prefer a more comfortable surface touch and a more gorgeous appearance. Therefore, the battery back cover with high brightness glass as the main material in the prior art can no longer meet the requirements of the majority of consumers. Summary of the invention

[0003] The object of the present invention is to provide an anti-glare glass cover plate with comfortable touch feeling.

[0004] In order to achieve the above-mentioned object, a first aspect of the present invention provides a glass, comprising: a glass body having irregular pits distributed on the outer surface; wherein the roughness of the glass is 0.8-1.2, and the haze is 70-85.

[0005] The glass body with irregular pits distributed on the outer surface of the present invention can present an anti-glare effect. The glass provided by the present invention has a comfortable touch feel and a good surface sand grain texture.

[0006] Optionally, the light transmittance of the glass is 88-91; and the diameter of the pit is 20-40 μm.

[0007] Optionally, the glass further includes a hydrophobic film layer attached to the outer surface of the glass body.

[0008] Optionally, the glass further comprises: a membrane attached to the inner surface of the glass body; the membrane comprises an ink layer coated on the outermost surface of the membrane.

[0009] Optionally, the membrane includes: a membrane substrate, a texture layer formed on a first surface of the membrane substrate, an electroplating layer formed on a first surface of the texture layer, and a first ink layer coated on the first surface of the electroplating layer.

[0010] Optionally, the glass further includes: a second ink layer coated on the inner surface of the glass body and an explosion-proof film attached to the inner surface of the second ink layer.

[0011] Optionally, the glass is microcrystalline glass; the glass body is a microcrystalline glass body; the microcrystalline glass body includes a microcrystalline glass substrate and a crystal layer formed on the outer surface of the microcrystalline glass substrate; the crystal layer has a thickness of 80 to 100 nm; wherein the haze of the microcrystalline glass is 70 to 80.

[0012] Optionally, the glass is conventional glass; the glass body is conventional glass body; wherein the haze of the conventional glass is 75-85.

[0013] The second aspect of the present invention provides a processing technology for anti-glare glass, the processing technology comprising: using a high-speed airflow containing corundum to perform sandblasting on the outer surface of a glass substrate to obtain a first glass having pits on the outer surface; performing chemical polishing on the outer surface of the first glass to obtain a second glass having an anti-glare effect on the outer surface; wherein the chemical polishing includes using a high-speed airflow containing H + Solutions containing OH - The outer surface of the first glass is chemically etched by a solution.

[0014] The present invention utilizes high-speed airflow to make fine-grained corundum hit the outer surface of the microcrystalline glass, so that its surface structure is continuously damaged by the impact of sand particles, forming tiny pits on the rough surface, which is the first step to achieve the velvet AG effect; the tiny pits generated by sandblasting are continuously reacted and amplified through chemical polishing to achieve certain roughness and haze requirements, thereby completing the overall velvet AG effect.

[0015] Optionally, the chemical polishing treatment includes etching the outer surface of the first glass using an HF solution generated by aging; the preparation method of the HF solution generated by aging includes: mixing a strong acid solution with an NH4HF2 solution and / or an NH4F solution and then letting it stand; the strong acid solution is selected from at least one of HCl, H2SO4 and HNO3.

[0016] Optionally, the glass substrate is microcrystalline glass; the chemical polishing process includes using a + The outer surface of the first glass is chemically etched with a solution; optionally, the processing technology also includes: performing an alkali washing treatment on the outer surface of the second glass to obtain a third glass; performing a first water polishing treatment on the outer surface of the third glass to obtain a fourth glass; performing a first strengthening treatment on the fourth glass to obtain a fifth glass; performing a second water polishing treatment on the outer surface of the fifth glass to obtain a sixth glass; performing a first coating treatment on the outer surface of the sixth glass to obtain a first glass cover plate having a hydrophobic film layer coated on the outer surface.

[0017] Optionally, the glass substrate is conventional glass; the processing technology also includes: performing a second strengthening treatment on the outer surface of the second glass to obtain a seventh glass; performing a second coating treatment on the outer surface of the seventh glass to obtain a second glass cover plate having a hydrophobic film layer coated on the outer surface.

[0018] A third aspect of the present invention provides a glass cover plate, wherein the glass cover plate comprises the aforementioned glass or glass prepared according to the aforementioned processing technology.

[0019] A fourth aspect of the present invention provides a device housing, the device housing comprising the aforementioned glass cover plate.

[0020] A fifth aspect of the present invention provides an electronic device, the electronic device comprising the aforementioned device housing or the aforementioned glass.

[0021] Through the above technical scheme, the anti-glare glass provided by the present invention has excellent anti-fingerprint effect, comfortable touch feel, and good surface sand texture, and can be applied to electronic device casings to improve the appearance, texture and touch of electronic device casings.

[0022] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0024] Figure 1 A schematic diagram of the glass in the present invention is shown, wherein the mark "1" represents a glass body with a plurality of irregular pits distributed on the outer surface, and the mark "2" represents a hydrophobic film layer.

[0025] Figure 2 An electron microscope image of the first glass having pits on its surface according to the present invention is shown.

[0026] Figure 3 The electron microscope image of the second glass with anti-glare effect in the present invention is shown.

[0027] Figure 4 An electron microscope image of an anti-glare glass prepared using microcrystalline glass as the glass body in an exemplary embodiment of the present invention is shown. Figure 4 The scale marked in the figure is the diameter of the pit formed by the impact of diamond grains under the electron microscope magnification.

[0028] Figure 5 An electron microscope image of an anti-glare glass prepared using conventional glass as the glass body in another exemplary embodiment of the present invention is shown. DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0030] In one embodiment of the present invention, the anti-glare glass (AG glass for short) is characterized in that the original reflective surface of the glass is changed into a matte non-reflective surface. Glass-ceramics is a polycrystalline solid phase material containing a glass body obtained by controlled nucleation and crystallization of certain basic glasses of specific composition at a certain temperature. It has the characteristics of both glass and ceramics. The main components are consistent with glass, but the microstructure is phase-changed to ceramics, and its density is the same as that of glass.

[0031] In one embodiment of the present invention, the material containing a crystalline phase is microcrystalline glass, and the material not containing a crystalline phase is ordinary glass.

[0032] The roughness in one embodiment of the present invention is the centerline average roughness, which is specifically calculated as follows: a length L is captured on the surface profile curve, the length is taken as the center as the X-axis, and the sum of the areas of all the oblique lines within the captured length is divided by the measured length L.

[0033] The haze in one embodiment of the present invention, also known as haziness, is the ratio of the diffuse transmission flux of the incident light that deviates from the incident direction by more than a certain angle after passing through the glass to the total transmission flux.

[0034] The transmittance in one embodiment of the present invention represents the percentage of the luminous flux transmitted through the glass and its incident luminous flux, and can be directly measured using a transmittance meter.

[0035] A first aspect of the present invention provides a glass, comprising: a glass body having a plurality of irregular pits distributed on the outer surface; wherein the roughness of the glass is 0.8-1.2, and the haze is 70-85.

[0036] The glass body with a plurality of irregular pits distributed on the outer surface of the present invention can present an anti-glare effect. The glass provided by the present invention has excellent anti-fingerprint effect, comfortable touch feeling and good surface sand grain texture.

[0037] In an exemplary embodiment of the present invention, the light transmittance of the glass is 88-91; and the diameter of the pit is 20-40 μm.

[0038] Exemplarily, the glass further comprises a hydrophobic film layer attached to the outer surface of the glass body. By attaching the hydrophobic film layer to the outer surface of the glass body, the anti-fingerprint effect of the glass can be effectively improved.

[0039] According to the present invention, in order to enhance the decorative effect of the glass, the glass may further include: a film attached to the inner surface of the glass body; the film includes an ink layer coated on the outermost surface of the film.

[0040] In an exemplary embodiment of the present invention, the diaphragm includes: a diaphragm substrate, a texture layer formed on the first surface of the diaphragm substrate, an electroplating layer formed on the first surface of the texture layer, and a first ink layer coated on the first surface of the electroplating layer. The first surface described in the present invention is the surface exposed to the outside when a new coating has not yet been formed on the surface, that is, most of it is the outer surface. In the present invention, the diaphragm substrate can be a PET substrate, on which a texture layer with different texture effects can be achieved through a UV transfer process, and then an electroplating layer is made on the surface of the texture layer to enrich the gloss and color effects, and finally a colored ink is silk-screened on the surface of the electroplating layer to obtain a complete diaphragm. In an exemplary embodiment of the present invention, the diaphragm can be contoured bonded to the glass and vacuum defoamed with the help of a 3D vacuum bonding machine to achieve a complete appearance decorative effect.

[0041] According to the present invention, the glass may further include: a second ink layer coated on the inner surface of the glass body. In this embodiment, the entire surface of the glass inner surface is directly sprayed with ink, and the ink color can be freely selected. This method is simple in process, highly efficient and color-stable, and is conducive to ensuring the consistency of mass-produced color. Exemplarily, in order to ensure safety, a layer of explosion-proof film may be attached to the inner surface of the second ink layer, and one or two lines of Gundam black ink may be screen-printed on the explosion-proof film, so as to ensure the adhesion of the adhesive auxiliary materials and the like and ensure the safety factor when the glass is broken.

[0042] In an exemplary embodiment of the present invention, the glass is a microcrystalline glass; the glass body is a microcrystalline glass body; the microcrystalline glass body includes a microcrystalline glass substrate and a crystal layer formed on the outer surface of the microcrystalline glass substrate; wherein the roughness of the microcrystalline glass is 0.8 to 1.2, and the haze is 70 to 80. In this embodiment, since the microcrystalline glass contains crystals in its structure, when the microcrystalline glass substrate is processed, part of the crystals will be exposed on the surface of the substrate, so a crystal layer will be formed on the surface of the substrate.

[0043] In another exemplary embodiment of the present invention, the glass is conventional glass; the glass body is conventional glass body; wherein the conventional glass has a roughness of 0.8-1.2 and a haze of 75-85.

[0044] A second aspect of the present invention provides a processing technology for anti-glare glass, the processing technology comprising:

[0045] Using a high-speed airflow containing corundum to sandblast the outer surface of the glass substrate to obtain a first glass having pits on the outer surface;

[0046] Performing chemical polishing on the outer surface of the first glass to obtain a second glass with an anti-glare effect on the outer surface;

[0047] Wherein, the chemical polishing treatment includes using a + Solutions containing OH - The outer surface of the first glass is chemically etched by a solution.

[0048] The present invention utilizes high-speed airflow to make fine-grained corundum hit the surface of the microcrystalline glass, so that its surface structure is continuously impacted and damaged by the sand particles, forming tiny pits on the rough surface, which is the first step to achieve the velvet AG effect; the tiny pits generated by sandblasting are continuously reacted and amplified through chemical polishing to achieve certain roughness and haze requirements, thereby completing the overall velvet AG effect.

[0049] In the embodiment of the present invention, the parameters of the corundum and the high-speed airflow can be adjusted according to the target effect. For example, the particle size of the corundum can be 28 to 32 μm; the linear velocity of the high-speed airflow containing corundum can be 0.5 m / min, the sandblasting pressure can be 0.35 MPa, and the spraying speed can be 320 cycle / min.

[0050] Exemplarily, the chemical polishing treatment includes etching the outer surface of the first glass using a HF solution generated by aging; the preparation method of the HF solution generated by aging may include: mixing a strong acid solution with an NH4HF2 solution and / or an NH4F solution and then letting it stand; the strong acid solution is selected from at least one of HCl, H2SO4 and HNO3. In the present invention, the outer surface of the glass is etched by HF generated by aging a strong acid solution with an NH4HF2 solution and / or an NH4F solution, and precipitated salts such as fluorosilicates or fluoroaluminates are generated by reaction, which accumulate on the surface of the glass, hinder further etching of HF, and make the surface of the glass have an uneven effect. Through differences in process control, crystal shape, size, and arrangement, different glittering effects will also be presented under the irradiation of light.

[0051] In an exemplary embodiment of the present invention, the glass substrate is microcrystalline glass; the chemical polishing treatment preferably includes using a + The outer surface of the first glass is chemically etched by a solution.

[0052] The processing technology using microcrystalline glass as the glass substrate in the present invention may also include:

[0053] performing an alkali washing treatment on the outer surface of the second glass to obtain a third glass;

[0054] Performing a first water polishing treatment on the outer surface of the third glass to obtain a fourth glass;

[0055] performing a first strengthening treatment on the fourth glass to obtain a fifth glass;

[0056] Performing a second water polishing treatment on the outer surface of the fifth glass to obtain a sixth glass;

[0057] The outer surface of the sixth glass is subjected to a first coating treatment to obtain a first glass cover plate having a hydrophobic film layer coated on the outer surface.

[0058] The process of the present invention can apply microcrystalline glass to the glass back cover, and make the microcrystalline glass have the texture and feel of velvet AG. By matching with textured film / spray ink, color and light and shadow effects are increased, so that the microcrystalline glass of velvet AG can have super anti-fingerprint effect, more obvious surface sand texture, and more comfortable touch feel, bringing users a more comfortable visual and tactile experience.

[0059] According to the present invention, the corrosion rates of glass crystals and amorphous materials are different after chemical polishing, resulting in many crystals of the microcrystalline glass being exposed, and a "thin film" with a refractive index greater than 1 is produced with air (the refractive index of air is 1), for example, a refractive index of 1.25. Since the refractive index is different from that of the glass substrate, there will be color changes. Due to the different thicknesses and colors, the mass production consistency of the glass appearance effect is poor, so this "thin film" needs to be thinned by alkaline washing to minimize color inconsistency. The alkaline washing treatment in the present invention may include contacting an alkaline solution with the outer surface of the second glass, wherein the alkaline solution may be NaOH, and the contact time may be 30 minutes.

[0060] In one embodiment of the present invention, water polishing is a modification process of the glass surface using a flexible polishing tool or other polishing medium. After the microcrystalline vitrification polishing and alkali washing treatment, there are some reactive compounds on the surface. The water polishing can remove the compounds, and simultaneously remove some defects such as sandblasting discoloration and dirt on the glass surface, and simultaneously improve the bonding strength between the glass substrate and the coating.

[0061] The glass strengthening treatment involved in one embodiment of the present invention can be to immerse the glass in a molten salt of alkali ions having a larger radius than that of the alkali metal ions. Specifically, the surface compressive stress is formed by using the radius difference of the two alkali metal ions to cause a "crowding" effect on the surface; internally, due to the interaction of forces, a central tension is formed; at the same time, the ion diffusion is not completely penetrated, and there is a stress layer depth; the formed stress layer will have a protective effect on the glass, improve the strength and bending and compression resistance of the glass, and achieve a strengthening effect.

[0062] The present invention can effectively reduce the surface energy of glass through the first coating treatment, wherein the coating in one embodiment of the present invention is an AF coating (Anti-Fingerprint), specifically a fluorine material coating.

[0063] In another exemplary embodiment of the present invention, the glass substrate is conventional glass; the processing technology also includes: performing a second strengthening treatment on the second glass to obtain a seventh glass; performing a second coating treatment on the outer surface of the seventh glass to obtain a second glass cover plate having a hydrophobic film layer coated on the outer surface. The glass strengthening treatment involved in the present invention can be immersing the glass in an alkali ion molten salt having a larger radius than that of the alkali metal ion. The second strengthening treatment can improve the strength and bending and compression resistance of the second glass. The present invention can effectively reduce the surface energy of the glass through the second coating treatment, wherein the coating in one embodiment of the present invention is an AF coating, specifically a fluorine material coating.

[0064] In one embodiment of the present invention, a high-speed airflow formed by an air compressor is used to hit fine-grained corundum (30±2μm) onto the surface of the microcrystalline glass, so that the surface structure of the microcrystalline glass is continuously damaged by the impact of sand particles, forming tiny pits on the rough surface, and obtaining a first glass. The HF solution generated by aging is used to continuously react and amplify the tiny pits generated by sandblasting on the surface of the first glass, so as to complete the overall effect of velvet AG and obtain a second glass. The second glass is impregnated with a NaOH solution to obtain a third glass, wherein the immersion time of the NaOH solution is 30 minutes. The third glass is subjected to a first water-polishing treatment using a water-polishing machine to obtain a fourth glass. The fourth glass is immersed in a sodium salt molten salt for strengthening treatment to obtain a fifth glass. The fifth glass is subjected to a first water-polishing treatment using a water-polishing machine to obtain a sixth glass. An AF film is coated on the outer surface of the sixth glass to obtain a microcrystalline glass with an anti-glare effect. The electron microscope image of the microcrystalline glass prepared in this embodiment is shown in FIG. Figure 4 As shown, the diameter of the pits distributed on the surface of the glass is 20-40 μm. The haze meter BYK4775 is used for haze detection, the contact roughness meter and profilometer are used for roughness detection, and the spectrophotometer Maya2000pro is used for transmittance detection. The haze range of the microcrystalline glass is 70-80, the roughness range is 0.8-1.2, and the transmittance is 88-91.

[0065] Another embodiment of the present invention utilizes a high-speed airflow formed by an air compressor to hit fine-grained corundum (30±2μm) onto the surface of conventional glass, so that the surface structure of the conventional glass is continuously damaged by the impact of the sand particles, forming tiny pits on the rough surface, thereby obtaining a first glass. The HF solution generated by aging is used to continuously react and amplify the tiny pits generated by sandblasting on the surface of the first glass, thereby completing the overall effect of velvet AG, thereby obtaining a second glass. The second glass is immersed in sodium salt molten salt for strengthening treatment to obtain a third glass. An AF film is coated on the surface of the third glass to obtain conventional glass with an anti-glare effect. An electron microscope image of the conventional glass prepared in this embodiment is shown in FIG. Figure 5The diameter of the pits distributed on the surface of the glass is 20-40 μm. The haze is measured by using a haze meter BYK4775, the roughness is measured by using a contact roughness meter and a profilometer, and the transmittance is measured by using a spectrophotometer Maya2000pro. The results show that the haze of the conventional glass ranges from 75 to 85, the roughness ranges from 0.8 to 1.2, and the transmittance is 88 to 91.

[0066] A third aspect of the present invention provides a glass cover plate, wherein the glass cover plate comprises the aforementioned glass or glass prepared according to the aforementioned processing technology.

[0067] A fourth aspect of the present invention provides a device housing, wherein the device housing comprises the aforementioned glass cover plate. The device housing of the present invention has a stronger anti-fingerprint effect and a more comfortable touch feel.

[0068] A fifth aspect of the present invention provides an electronic device, the electronic device comprising the aforementioned device housing or the aforementioned glass.

[0069] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the present invention. The present invention is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The description and examples are to be considered as exemplary only, and the true scope and spirit of the present invention is indicated by the following claims.

[0070] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A glass, characterized in that: include: A glass body with a plurality of irregular pits distributed on the outer surface; wherein the roughness of the glass is 0.8-1.2 and the haze is 70-85.

2. The glass according to claim 1, characterized in that The light transmittance of the glass is 88-91; and / or the diameter of the pit is 20-40 μm.

3. The glass according to claim 1, characterized in that The glass further comprises a hydrophobic film layer attached to the outer surface of the glass body.

4. The glass according to claim 1, characterized in that The glass further comprises: a film attached to the inner surface of the glass body; the film comprises an ink layer coated on the outermost surface of the film.

5. The glass according to claim 4, characterized in that The membrane comprises: a membrane substrate, a texture layer formed on a first surface of the membrane substrate, an electroplating layer formed on a first surface of the texture layer, and a first ink layer coated on a first surface of the electroplating layer.

6. The glass according to claim 1, characterized in that The glass further comprises: a second ink layer coated on the inner surface of the glass body and an explosion-proof film attached to the inner surface of the second ink layer.

7. The glass according to claim 1, characterized in that The glass is glass-ceramics; the glass body is a glass-ceramics body; the glass-ceramics body comprises a glass-ceramics substrate and a crystal layer formed on the outer surface of the glass-ceramics substrate; the crystal layer has a thickness of 80 to 100 nm; Wherein, the haze of the microcrystalline glass is 70-80.

8. The glass according to claim 1, characterized in that The glass is conventional glass; the glass body is conventional glass body; Wherein, the haze of the conventional glass is 75-85.

9. A glass processing process, characterized in that: The processing technology includes: Using a high-speed airflow containing corundum to sandblast the outer surface of the glass substrate to obtain a first glass having pits on the outer surface; Performing chemical polishing on the first glass to obtain a second glass with an anti-glare effect on the outer surface; Wherein, the chemical polishing treatment includes using a + Solutions containing OH - The outer surface of the first glass is chemically etched by a solution.

10. The processing technology according to claim 9, characterized in that: The chemical polishing treatment includes etching the outer surface of the first glass using an HF solution generated by aging; The method for preparing the HF solution generated by aging comprises: mixing a strong acid solution with an NH4HF2 solution and / or an NH4F solution and then allowing the mixture to stand; The strong acid solution is selected from at least one of HCl, H2SO4 and HNO3.

11. The processing technology according to claim 9, characterized in that: The glass substrate is microcrystalline glass; the chemical polishing process includes using a + chemically etching the outer surface of the first glass with a solution; The processing technology also includes: performing an alkali washing treatment on the outer surface of the second glass to obtain a third glass; Performing a first water polishing treatment on the outer surface of the third glass to obtain a fourth glass; performing a first strengthening treatment on the fourth glass to obtain a fifth glass; Performing a second water polishing treatment on the outer surface of the fifth glass to obtain a sixth glass; The outer surface of the sixth glass is subjected to a first coating treatment to obtain a first glass cover plate having a hydrophobic film layer coated on the outer surface.

12. The processing technology according to claim 9, characterized in that: The glass substrate is conventional glass; The processing technology also includes: performing a second strengthening treatment on the second glass to obtain a seventh glass; The outer surface of the seventh glass is subjected to a second coating treatment to obtain a second glass cover plate having a hydrophobic film layer coated on the outer surface.

13. A glass cover plate, characterized in that: The glass cover plate comprises the glass according to any one of claims 1 to 8 or the glass prepared by the processing technology according to any one of claims 9 to 12.

14. A device housing, characterized in that: The device housing comprises the glass cover plate of claim 13.

15. An electronic device, characterized in that: The electronic device comprises the device housing according to claim 14, or comprises the glass according to any one of claims 1 to 8.